A biopsychosocial network model of fatigue in rheumatoid arthritis: a systematic review. (4th November 2019) - Geenen, Rinie; Dures, Emma
Abstract: Fatigue in RA is prevalent, intrusive and disabling. We propose a network model of fatigue encompassing multiple and mutually interacting biological, psychological and social factors. Guided by this model, we reviewed the literature to offer a comprehensive overview of factors that have been associated with fatigue in RA. Six categories of variables were found: physical functioning, psychological functioning, medical status, comorbidities and symptoms, biographical variables and miscellaneous variables. We then systematically reviewed associations between fatigue and factors commonly addressed by rheumatology health professionals. Correlations of fatigue with physical disability, poor mental well-being, pain, sleep disturbance and depression and anxiety were ∼0.50. Mostly these correlations remained significant in multivariate analyses, suggesting partly independent influences on fatigue and differences between individuals. These findings indicate the importance of research into individual-specific networks of biopsychosocial factors that maintain fatigue and tailored interventions that target the influencing factors most relevant to that person.